AFFECTIVENESS IN FAMILY LAW: ASPECTS REGARDING NARCISSISTIC PERSONALITY DISORDER (REMUNOM, 2023)
This article aims to analyze the consequences of narcissistic personality disorder in the context of Family Law. The focus will be on the relational dynamics between a mother who has this disorder and her child, as well as the characteristics that result from this pathology. Furthermore, the damage caused to the emotional and psychological development of children born to narcissistic mothers will also be investigated, as well as aspects of self-esteem and self-image. Another point that will be addressed is how the child's social and family relationships will be affected and how affection is consolidated in the relationship with this mother. In developing the article, current legislation will be used, in addition to doctrinal citations, clinical research studies and interviews, for the basis of a reasoned understanding of the subject.